Non-enzymatic roles of human RAD51 at stalled replication forks - Jennifer M. Mason (Nature Portfolio, 2019)
RAD51 has been implicated in replication fork processing and restart in response to replication stress. Here, authors reveal mechanistic aspects of non-enzymatic roles of RAD51 for fork reversal and cooperation with FBH1.